Publicly Funded Transport Research in the P. R. China, Japan, and Korea Policies, Governance and Prospects for Cooperation with the Outside World - Giannopoulos, George A.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book discusses transport research and innovation, highlighting prospects for cooperation between different countries. To create a basis for such cooperation, the book first describes the status quo in individual countries, focusing on China, Japan and Korea, and identifies the main technological trends as well as current innovation policies in these countries, discussing their main advantages and the challenges to establishing collaborations between them. The book is a valuable resource for transport researchers, research authorities and transport organizations, not only in the three countries considered, but also in the US and the EU. By providing a revealing snapshot of current transport research and policies, it fosters exchanges and collaborations between nations.
Preface -- Chapter I: The Case for Cooperation With China, Japan, Korea in Transport Research - Rationale for this Book and Summary of its Findings -- Chapter ii: The Changing Context of Transport Research -- Chapter iii: Publicly Funded Research and Innovation In The P. R. China And The Outlook For International Cooperation -- Chapter Iv: Publicly Funded Research and Innovation In Japan and the Outlook for International Cooperation -- Chapter V: Publicly Funded Research and Innovation In Korea and the Outlook for International Cooperation.
Keywords: Transportation engineering; Traffic engineering; Technological innovations; Political science; Service industries; Transportation Technology and Traffic Engineering; Innovation and Technology Management; Governance and Government; Services